O princípio da solidariedade e as contribuições sociais: limites e possibilidades de incidência na Constituição federal de 1988 - Gonçalves, Marlo Thurmann (Universidade do Vale do Rio dos Sinos, 2014)
From the issue about the legal possibility that the scope of application of social contributions contained in the Constitution be interpreted from the principle of solidarity, shows the evolution of the model of State, up to the present days, named Law Democratic State, brings practical consequences to political and juridical extent. The insertion of the element named “democracy” to the concept of Law Democratic State brings about to the State the duty of promoting conditions for the full practice of citizenship by all citizens.The action of the State legitimates itself in the achievement of constitutional values and principles. Among them stands out the principle of solidarity, raised up by the constitution as the fundamental aim of the Republic. Such principle imposes on part of the citizens the duty of acting with solidarity in behalf of the lesser ones to provide them material conditions that qualify them to become citizens in its full sense overcoming economic and social vulnerability. Indeed, the research object of this dissertation, inserted into the search area Hermeneutics, Constitution and Implementation of Rights, is that to understand how to give the proper interpretation of contributions in accordance with the principle of solidarity, establishing its limits and possibilities of application. Elevated to the condition of fundamental principle of the Republic, the principle of solidarity perpasses the juridical tributary relations, conditioning the understanding of the different tributes in accordance to the essential characteristics of each kind of tribute. It applies essentialy to social taxation which has its validity based on being assured as a social constitutional aim. From the analysis of such tributary type in consonancy to the principle of solidarity, it results in the applicability of the principle of the ability to pay upon it. It follows that solidarity is a structural principle, thus it cannot be required the taxation only from a specific group of taxpayers directly or indirectly linked to the beneficiaries. The conclusion is that, in spite of the application of the principle, the institution of social taxes is subjected to specific limits such as the prohibition of forfeiture, the dignity of human beings, and the semantical limits of constitutional rules that grant imposing competency to the members of the Federation.
Keywords: Tributação; Estado democrático de direito; Solidariedade; Princípio da capacidade contributiva; Contribuições sociais; Taxation; Law democratic state; Solidarity; Principle of ability to pay; Social taxation; ACCNPQ::Ciências Sociais Aplicadas::Direito